PERANAN AKUNTANSI DALAM MEMPERSEMPIT PERBEDAAN ANTARA KELOMPOK KAYA DAN MISKIN AKIBAT GLOBALISASI - Muliawati . (Bina Ekonomi, 2014)
Globalisation is a process in which national economies become integrated into global economy. Globalisation brings benefits and opportunities such as reducing the unemployment rate and poverty. However there are many critics about globalisation. One of them is that it widen the gap between the haves and the have-nots in a country. High quality of global financial reporting can be achieved through the implementation of IFRS. It helps users (investors and creditors) in making decisions related to the allocation of resources, especially to companies in their country or in other countries. Hopefully, resource allocation in the era of globalisation can be done effectively and efficiently. For many years, in developing countries and poor countries the number of unskilled labor much more than the skilled labor. This led to formation of gap between the haves and the have-nots. Now, companies are expected not only looking for profit, but must pay attention to human resources (people) and environment (planet) as well. Companies should play an active role to improve the quality of human resources. So, the number of unskilled labor will be reduced and skilled labor is increased. Commonly, skilled labor will receive higher benefits (salaries) than the unskilled labor. Therefore, if the number of skilled labor increasing, the gap between the haves and the have-nots will be narrowed.